Application of targeted 2D planar chromatography in the control of ginkgolic acids in some herbal drugs and dietary supplements - Migas Piotr; Romańczuk Anna; Szumacher Marta; Krauze-Baranowska Mirosława (Acta Pharmaceutica)
Two-step targeted 2D planar chromatographic method (2DTLC) was used in the determination of ginkgolic acids in pharmaceuticals and dietary supplements. The choice of the extraction method and the separation technique was guided by the formulation type (capsule, tablet, tincture) with expected low amounts of ginkgolic acids in the analyzed herbal samples. Separation of ginkgolic acids C15:1 and C17:1 on HPTLC RP18 WF254s was preceded by its separation from the sample matrix on TLC Si60 F254s. Mobile phases consisted of acetonitrile/water/formic acid (80:20:1, V/V/V) and n-heptane/ethyl acetate/formic acid (20:30:1, V/V/V), resp. Identification of separated compounds was based on 2D-TLC co-chromatography with reference substances and off-line 2D-TLC x HPLC-DAD-ESI-MS analysis. Quantification of ginkgolic acids C15:1 and C17:1 was conducted densitometrically. Among the analyzed products, the presence of ginkgolic acids was confirmed only in herbal drugs containing 60 % ethanolic tinctures of Ginkgo biloba leaves. The use of TLC in the quantification of ginkgolic acids C15:1 and C17:1 in ginkgo extracts was described for the first time.